Pendampingan Pemanfaatan Sampah Organik Menjadi Eco-Enzyme Sebagai Upaya Pengurangan Sampah di Lingkungan Sekolah - Supriyanto, Supriyanto; Maflahah, Iffan; Rahman, Askur; Hidayati, Darimiyya; Mojiono, Mojiono; Faridz, Raden; Lestari, Heny (Jurnal Ilmiah Pangabdhi, 2023)
The increase in the number of inhabitants is in line with the increase in the amount of domestic waste generated. One of the efforts to overcome domestic waste is the manufacture of eco-enzymes that can be applied at the household level. Eco-enzyme is a liquid extract produced from the fermentation of vegetable and fruit residues with a brown sugar substrate.  The purpose of this assistance is to provide an understanding and increase the awareness and skills of students of SMA Muhammadiyah 2 Surabaya in processing organic waste into eco- enzyme products. The implementation stages of the activity are divided into 4 stages, namely the preparation, implementation, evaluation, and monitoring stages. The results of the activity showed that students of Muhammadiyah Dua High School Surabaya were generally satisfied with the training topics, training topics, speaker competencies, material delivery techniques, training duration and props or facilities. In addition, 61.1% of students stated that this mentoring was very useful, 30.6% mentioned it was beneficial and 8.3% stated that this training was quite useful. The resulting recommendation is that after the fermentation process is complete, it is necessary to re-assist the eco-enzyme harvesting process and the use of eco enzymes